Curriculum mathematics practice 5 - Ledsham, A.; Elvin, R.; Bindley, M. (New York : Oxford university press, 1998)
A series of six books that complements the skills practice for students aged between 11 and 16. It covers levels 3 to 8 of the National Curriculum, with the level of difficulty increasing through the six books. It features: basic explanations of the mathematics; and worked examples and exercises to help students to consolidate their understanding.
Keywords: Mathematics -- Problems, exercises, etc